Polskie modele do prognozowania bankructwa przedsiębiorstw i ich weryfikacja - Kisielińska, Joanna; Waszkowski, Adam (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The paper presents 17 models of developed corporate bankruptcy prediction for the Polish economy. These were the model of Hołda [2001], Gajdka and Stos [2003], two models of Prusak [2005], seven models of Mączyńska and Zawadzki [2006], Wierzba [2000], Harmol, Czajka and Piechocki [2004] and four models of Gruszczyński [2003]. The effectiveness of models was verifi ed for the 8 companies that went bankrupt during the period 2003–2008 and 8 firms in good financial condition. Studies have shown that the quality of the resulting classification was satisfactory only for six models. In the remaining cases there was too low proportion of correct identification, or too strong asymmetry in the diagnosis classes. If, however, were considered to indicate all the analyzed models, it turned out that 14 companies recognized correctly most of them. Individual companies correctly classified from 65 to 100% of the models. Research has shown that poor performance gave the classification model using a small number of financial indicators.